2023
DOI: 10.1007/s00167-023-07435-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior tibial slope, notch width index and tibial tubercle to trochlear groove distance contribute to development of mucoid degeneration of the anterior cruciate ligament: a systematic review

Abstract: PurposeTo determine what knee morphological factors are associated with the development of mucoid degeneration of the anterior cruciate ligament (ACL). Methods Three databases MEDLINE, PubMed and EMBASE were searched from inception to January 29th, 2023 for literature outlining knee morphological factors that potentially lead to the development of mucoid degeneration of the ACL. The authors adhered to the PRISMA and R-AMSTAR guidelines as well as the Cochrane Handbook for Systematic Reviews of Interventions. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Only one study demonstrated a relationship between r m and PCL rupture. PTS has been investigated thoroughly concerning its role as a risk factor for a variety of pathological conditions of the knee, including primary and secondary ACL tears as well as mucoid degeneration of the ACL [28,29]. There is a lack of consensus surrounding normal and pathological values for PTS.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study demonstrated a relationship between r m and PCL rupture. PTS has been investigated thoroughly concerning its role as a risk factor for a variety of pathological conditions of the knee, including primary and secondary ACL tears as well as mucoid degeneration of the ACL [28,29]. There is a lack of consensus surrounding normal and pathological values for PTS.…”
Section: Discussionmentioning
confidence: 99%
“…They had retrospectively studied 11 knees that underwent total excision of mucoid-degenerated ACL and noted that 10 knees had medial compartment arthritis and eight had a medial meniscus tear [ 12 ]. Many other bony factors are also implicated in the pathogenesis of the mucoid ACL, such as increased posterior slope, decreased notch width index, increased tibial tuberosity-trochlear groove distance, and trochlear dysplasia [ 20 ]. However, we have not assessed any of those bony factors as several MRIs were not performed in our hospital, limiting the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to these established criteria, comparative studies can receive a maximum of 24 [33]. The quality of comparative studies was classified as follows: 0-6 very low quality, 7-10 low quality, 11-15 fair quality, 16-20 good quality and ≥ 20 high quality [38]. The quality of randomised control trials (RCTs) was assessed using the Detsky Quality Assessment Scale [9].…”
Section: Quality Assessmentmentioning
confidence: 99%